Heart of Borneo Series 5 : Proceedings of Heart of Borneo Seminar - Tama Abu - Meekiong, Bin Kalu (Forest Department Sarawak, 2019)
This Proceedings gives us a glimpse on the findings of the Scientific Expedition to Tama Abu PF made in 2017 which was organized by the Forest Department of Sarawak. This book is the fifth in a Heart of Borneo Series publication under the Heart of Borneo Project Initiative for Sarawak. It highlights part of the findings of the 2017 expedition that presented during the Heart of Borneo Seminar 2018. A total of twenty-one papers, that includes flora (11), fauna (9) and one paper each on microbial and geological that part of the findings of the expedition were presenting in this Seminar Proceedings book. While other findings will be included in the pictorial coffee-table book (Heart of Borneo Series 7).